ANALISIS JARAK PELEDAKAN KUARI ANDESIT TERHADAP REL KERETA API CEPAT DI CV PANGHEGAR PLERED PURWAKARTA JAWA BARAT - Adinugraha, Wanda; Suwandhi, Awang; Marmer, Dwihandoyo; Hartami, Pantjanita Novi; Ipmawati, Meda Rusdiana (PPSDM Geominerba, 2024)
CV Panghegar, operating in the villages of Cilalawi and Liunggunung, Sukatani and Plered sub-districts, Purwakarta Regency, West Java Province, is a quarry mining company that employs blasting activities to break andesite rock in its mining processes. Given the proximity of the high-speed railway tracks to the mining site, a technical assessment of the impact of blasting is necessary. The distance between the high-speed railway tracks and the mining site, being less than 300 meters, presents a critical issue as blasting vibrations or flyrock can damage the railway structure or pose a safety hazard to passing trains during blasting operations. The objectives of this study are to determine the safe ground vibration levels caused by blasting, the safe distance for flyrock, and the methods and technical references for safe blasting activities near high-speed railway tracks within 300 meters. The study approach includes field observations, measurements, and discussions with the company and other relevant parties. Based on the study results, it is concluded that the maximum vibration levels are below the standard vibration limits, with vibrations towards the tracks at distances of 58 meters and 60 meters reaching 13.61 mm/s and 15.86 mm/s, respectively. Meanwhile, the maximum vibration levels parallel to the tracks at distances of 56 meters and 62 meters reach 15.2 mm/s and 17.69 mm/s, respectively. The farthest flyrock distance is 20-30 meters (< 300 meters). Blasting operations with the current geometry and at a distance of 100 meters (< 300 meters) from the railway tracks can use a maximum ANFO explosive weight of 22.5 kg/delay (equivalent to 3 holes detonating simultaneously), 37.5 kg/delay (equivalent to 5 holes detonating simultaneously), or 52.5 kg/delay (equivalent to 7 holes detonating simultaneously), which are predicted to generate vibrations of 8.15 mm/s, 12.90 mm/s, and 17.47 mm/s, respectively.